2021
DOI: 10.3389/fpls.2021.716750
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Amplified Repetitive Sequences Among Aegilops tauschii Subspecies and Genotypes

Abstract: Genomic repetitive sequences commonly show species-specific sequence type, abundance, and distribution patterns, however, their intraspecific characteristics have been poorly described. We quantified the genomic repetitive sequences and performed single nucleotide polymorphism (SNP) analysis between 29 Ae. tauschii genotypes and subspecies using publicly available raw genomic Illumina sequence reads and used fluorescence in situ hybridization (FISH) to experimentally analyze some repeats. The majority of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…From another side, chromosomal breaks causing chromosomal rearrangements often occur at sites enriched with repetitive DNA (Raskina et al, 2008;Molnár et al, 2011;Murat et al, 2017;Pollak et al, 2018). Owing to this, many researchers studying genome evolution and speciation in plants were focused on analysis repetitive DNA (Liu et al, 2019;Song et al, 2020;Ebrahimzadegan et al, 2021;Waminal et al, 2021). Fluorescence in situ hybridization is one of the most broadly exploited approaches in this field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From another side, chromosomal breaks causing chromosomal rearrangements often occur at sites enriched with repetitive DNA (Raskina et al, 2008;Molnár et al, 2011;Murat et al, 2017;Pollak et al, 2018). Owing to this, many researchers studying genome evolution and speciation in plants were focused on analysis repetitive DNA (Liu et al, 2019;Song et al, 2020;Ebrahimzadegan et al, 2021;Waminal et al, 2021). Fluorescence in situ hybridization is one of the most broadly exploited approaches in this field.…”
Section: Discussionmentioning
confidence: 99%
“…strangulata and D subgenome chromosomes of common wheat differed from that in the D 1 and D 2 chromosomes, suggesting that these differences may exist in the genome of diploid progenitor. This assumption is legitimate, as many molecular ( Luo et al, 2007 ; Wang et al, 2013 ; Li et al, 2018 ; Singh et al, 2019 ; Gaurav et al, 2021 ) and cytogenetic ( Majka et al, 2017 ; Zhao et al, 2018 ; Badaeva et al, 2019a ; Ebrahimzadegan et al, 2021 ) data supported significant genome divergence between two Ae . tauschii subspecies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tauschii. Chromosomes of these species contain only little amounts of microsatellite sequences or do not possess them at all (Badaeva et al 2015a(Badaeva et al , 2019aLinc et al 2017;Li et al 2018;Zhao et al 2018;Ebrahimzadegan et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, differences in the proximity of retrotransposons to genes could contribute to the significant phenotypic differences between wild and cultivated sunflowers [43]. Recently, Ebrahizadegan et al [44] reported that different classes of repetitive DNA sequences have differentially accumulated between Aegilops tauschii subsp. strangulata and the other two subspecies of Ae.…”
Section: Discussionmentioning
confidence: 99%